Quantitative MRI Assessment of Supraspinatus Tendon Remodeling Following a Single Platelet-Rich Plasma Injection Using T2 Mapping and Relaxation Time Profiling - Karlo Pintarić; Andrej Vovk; Vladka Salapura; Žiga Snoj; Jernej Vidmar (Diagnostics)
Background: Quantitative magnetic resonance imaging (MRI) techniques such as T2 mapping may detect early tendon changes following biologic therapies. This study aimed to assess the structural remodeling of the supraspinatus tendon using mean T2 values and T2 distribution profiles after an ultrasound (US)-guided single platelet-rich plasma (PRP) injection. Methods: Twenty-six patients with symptomatic supraspinatus tendinopathy were divided into tendinosis (n = 9) and partial tear (n = 13) groups. T2 mapping and clinical evaluations (shoulder pain and disability index questionnaire (SPADI), Constant-Murley score) were conducted at baseline and 6 months post-PRP. Mean T2 values were measured in three tendon segments (lateral, middle, and medial), and T2 profiles were compared to asymptomatic controls. Results: Clinical outcomes showed significant improvement in both the tendinosis and partial tear groups at the 6-month follow-up. Although no significant changes were observed in the mean T2 relaxation times across tendon segments following PRP treatment, T2 distribution profiling revealed statistically significant alterations in both groups. In the tendinosis group, post-treatment T2 profiles approached those of the asymptomatic controls, suggesting structural remodeling consistent with tendon healing. Conclusions: T2 mapping is an effective tool for detecting tendon remodeling following PRP therapy. Structural improvements indicative of tissue healing were observed in cases of tendinosis, but not in partial tendon tears. These findings support the use of T2 mapping—particularly the T2 distribution profiling—as a quantitative biomarker for assessing treatment response to PRP.